Identifying SARS-CoV2 transmission cluster category: An analysis of country government database. Issue 4 (April 2021) - Fouda, Basem; Tram, Ha P.B.; Makram, Omar M.; Abdalla, Abdelrahman S.; Singh, Tushar; Hung, I-Chun; Raut, Akshay; Hemmeda, Lina; Alahmar, Majd; ElHawary, Ahmed S.; Awad, Dina M.; Huy, Nguyen T.
Abstract: Background: As a result of the high contagiousness and transmissibility of SARS-CoV-2, studying the location of the case clusters that will follow, will help understand the risk factors related to the disease transmission. In this study, we aim to identify the transmission cluster category and settings that can guide decision-makers which areas to be opened again. Methods: A thorough review of the literature and the media articles were performed. After data verification, we included cluster data from eight countries as of 16th May 2020. Clusters were further categorized into 10 categories and analysis was performed. The data was organized and presented in an easily accessible online sheet. Results: Among the eight included countries, we have found 3905 clusters and a total number of 1, 907, 944 patients. Indoor settings (mass accommodation and residential facilities) comprised the highest number of both number of clusters (3315/3905) and infected patients (1, 837, 019/1, 907, 944), while the outdoor ones comprised 590 clusters and 70, 925 patients. Mass accommodation was associated with the highest number of cases in 5 of the 7 countries with data available. Social events and residential settings were responsible for the highest number of cases in the two remaining countries. In the USA, workplace facilities have reported 165 clusters of infection including 122 food production facilities. Conclusions: Lockdown could truly be a huge burden on a country's economy. However, with the proper knowledge concerning the transmissibility and the behaviour of the disease, better decisions could be made to guide the appropriate removal of lockdown across the different fields and regions.